A viabilidade de um projeto sustentável em assentamentos rurais de reforma agrária - Andréia Terzariol Couto (Sociedade & Natureza)
The subject of this paper is to present the results of a research that took place in an agrarian reform settlement named Rio das Pedras, in Uberlândia, Minas Gerais, and it discuss the possibility of elaborate and grow an agriculture sustainable project in this area. O trabalho also introduces some discussions in relation to the social and enviromental characterização, and the possibility to develop this kind of agriculture among the small farmers in the settlement.